2001
DOI: 10.1074/jbc.m006864200
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Mature ErbB2 to Geldanamycin Is Conferred by Its Kinase Domain and Is Mediated by the Chaperone Protein Hsp90

Abstract: ErbB receptors are a family of ligand-activated tyrosine kinases that play a central role in proliferation, differentiation, and oncogenesis. ErbB2 is overexpressed in >25% of breast and ovarian cancers and is correlated with poor prognosis. Although ErbB2 and ErbB1 are highly homologous, they respond quite differently to geldanamycin (GA), an antibiotic that is a specific inhibitor of the chaperone protein Hsp90. Thus, although both mature and nascent ErbB2 proteins are down-regulated by GA, only nascent ErbB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
292
2
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(323 citation statements)
references
References 29 publications
26
292
2
3
Order By: Relevance
“…Proteosomal degradation of the dimer partner ErbB2 is limited by the ATP-sensitive chaperone function of Hsp90 (Xu et al, 2001), thus reductions in cellular ATP result in ErbB2 dissociation and degradation (Peng et al, 2005).…”
Section: Ischaemia and Ischaemic Heart Diseasementioning
confidence: 99%
“…Proteosomal degradation of the dimer partner ErbB2 is limited by the ATP-sensitive chaperone function of Hsp90 (Xu et al, 2001), thus reductions in cellular ATP result in ErbB2 dissociation and degradation (Peng et al, 2005).…”
Section: Ischaemia and Ischaemic Heart Diseasementioning
confidence: 99%
“…GA-induced degradation of ErbB2 can be inhibited by proteasomal inhibitors (Mimnaugh et al, 1996), and a straightforward interpretation of this is that ErbB2 is degraded by the proteasome itself (Hong et al, 1999;Zheng et al, 2000;Xu et al, 2001;Citri et al, 2002;Way et al, 2004). We recently demonstrated that proteasomal activity is needed for GAinduced internalization and lysosomal degradation of ErbB2 (Lerdrup et al, 2006).…”
Section: Proteasomal Activity Is Needed For Cleavage Of Erbb2mentioning
confidence: 99%
“…[18][19][20] Importantly, HA and GA had no direct effect on tyrosine kinase activity in an immune complex assay in vitro. 21 A solid phase-immobilized GA derivative and affinity experiments revealed that the molecular target of GA is Hsp90.…”
Section: Introductionmentioning
confidence: 99%